The Affiliation of Sargonic Akkadian with Babylonian and Assyrian: New Insights Concerning the Internal Sub-Grouping of Akkadian - Hasselbach, Rebecca (Journal of Semitic studies, 2007)
The affiliation of Sargonic Akkadian with Babylonian and Assyrian is still a matter of dispute. It has recently been suggested that Sargonic Akkadian is not related to any of the later dialects but constitutes an independent dialect that died out after the downfall of the Akkadian dynasty. In this article, the author reinvestigates the major phonological and morphological features of Sargonic Akkadian and tries to determine whether isoglosses with later dialects represent shared retentions or shared innovations. The investigation leads to the conclusion that most of the grammatical features that were previously used in favour of a separation of Sargonic Akkadian from Babylonian and/or Assyrian should be considered shared retentions. Consequently, they have no significant value for the sub-grouping of Akkadian. Furthermore, certain sub-corpora of Sargonic Akkadian share significant innovations with Babylonian and should be analysed as an early predecessor of this dialect.